Keberadaan Mikroorganisme Tanah pada Areal Rehabilitasi Takino Soil Protection Sheet dan Kemampuan Menahan Erosi Permukaan di Kaldera Gunung Batur - I NYOMAN TRYADI CAHYA NUGRAHA; MADE SRITAMIN; I GEDE PUTU WIRAWAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2017)
Existence of Microorganism On Rehabilitation Area by Takino Soil Protection Sheet and Capability to Resist Soil Erosion in the Vulcanic Devastated Site in Mt. Batur The goal of this research was to know the existence of microorganism on rehabilitation area of Takino Soil Protection Sheet (TSPS) and capability to resist soil erosion in the vulcanic devastated site of Mt. Batur. This research used total plate count method to obtain mikroorganism colony, soil separating method to obtain mycorrhizal fungi spores, staining root method to find out percentage of mycorrhizal fungi spores on the roots and capability to resist erosion by measuring the soil trapped on the TSPS. The isolation results showed the number of bacteria colonies has been increase as much as 123%, while the number of fungi spores also increase as much as 100% in the area covered by TSPS. The results of trapping mycorrhizal fungi spores on the area covered by TSPS is 63/100g soil, in the area non covered by TSPS is 21/100g soil. The percentage of mychorrizal fungi infection in the plant roots on the area covered by TSPS is 27,5%. The result showed the average capability of TSPS to resist erosion is 5,26 cm over 3 years after implementation of TSPS.